HIV-1 protease-induced apoptosis - Rumlová, Michaela; Křížová, Ivana; Keprová, Alena; Hadravová, Romana; Doležal, Michal; Strohalmová, Karolína; Pichová, Iva; Hájek, Miroslav; Ruml, Tomáš (Retrovirology, 2014)
BACKGROUND: Apoptosis is one of the presumptive causes of CD4+ T cell depletion during HIV infection and progression to AIDS. However, the precise role of HIV-1 in this process remains unexplained. HIV-1 protease (PR) has been suggested as a possible factor, but a direct link between HIV-1 PR enzymatic activity and apoptosis has not been established. RESULTS: Here, we show that expression of active HIV-1 PR induces death in HeLa and HEK-293 cells via the mitochondrial apoptotic pathway. This conclusion is based on in vivo observations of the direct localization of HIV-1 PR in mitochondria, a key player in triggering apoptosis. Moreover, we observed an HIV-1 PR concentration-dependent decrease in mitochondrial membrane potential and the role of HIV-1 PR in activation of caspase 9, PARP cleavage and DNA fragmentation. In addition, in vitro data demonstrated that HIV-1 PR mediates cleavage of mitochondrial proteins Tom22, VDAC and ANT, leading to release of AIF and Hsp60 proteins. By using yeast two-hybrid screening, we also identified a new HIV-1 PR interaction partner, breast carcinoma-associated protein 3 (BCA3). We found that BCA3 accelerates p53 transcriptional activity on the bax promoter, thus elevating the cellular level of pro-apoptotic Bax protein. CONCLUSION: In summary, our results describe the involvement of HIV-1 PR in apoptosis, which is caused either by a direct effect of HIV-1 PR on mitochondrial membrane integrity or by its interaction with cellular protein BCA3.
Keywords: nádorový supresorový protein p53; Cell Line; jaderné proteiny; nádorové buněčné linie; apoptóza; mitochondrie; HEK293 Cells; Nuclear Proteins; protein X asociovaný s bcl-2; adaptorové proteiny signální transdukční; fragmentace DNA; DNA Fragmentation; HIV-1; HeLa Cells; Promoter Regions, Genetic; HIV infekce; Tumor Suppressor Protein p53; Cell Line, Tumor; bcl-2-Associated X Protein; Mitochondrial Proteins; Adaptor Proteins, Signal Transducing; HEK293 buňky; Humans; CD4-Positive T-Lymphocytes; HIV Protease; HIV-proteasa; promotorové oblasti (genetika); Mitochondria; buněčné linie; CD4-pozitivní T-lymfocyty; HIV Infections; mitochondriální proteiny; HeLa buňky; lidé; Apoptosis